Proposta de uma classificação de riscos em cadeias de suprimentos: uma aplicação no setor sucroalcooleiro. - Oliveira, Taiane Kamel de (2012)
The objective of this study was to contribute to the field of Supply Chain Management with an emphasis on identifying, prioritizing and measuring risk proposing a risk rating based on the SCOR model and investigating which of them involve two members of a supply chain of this sector. For the construction of the classification was carried out a theoretical classifications as reported in the literature and, using the basic processes advocated by the SCOR model as a foundation, a structured classification was proposed starting from the previously identified. Following a qualitative approach the study used direct observation, documents provided by the companies, unstructured interviews, and especially forms as research tools to determine what risks concern the studied chain members. Through the construction of risk matrices, analysis of variables and situations present in separate forms in a way, it was found that in one of the members of the most significant risks were operational, strategic and supplies, and another member of the risks of supply, financial and demand reached the highest levels of importance. Thus, the study shows the effect of risk on the chain as a whole to find the risks of supply and demand in the members that match the customer and supplier, respectively. In addition, the study sought to highlight the impact of identified risks linking them to the organizations costs and the result showed that the risks interfere mainly in management costs. From this result, one proposed a combination of risks to costs for a general situation. It s recommended to replicate the study in others chains, to continue within organizations that have been studied (with regard to monitor risks) and the expansion of such research to other supply chain members.